Comparative study of Pure and D-Malic Acid Doped Potassium Boro Oxalate Crystal: Special Attention on the Structural, Optical, Thermal, and Nonlinear Optical Properties - D. Yadav, S.; Baig, M. I.; Anis, M. (Journal of Scientific Research, 2025)
Single crystals of potassium boro oxalate (KBO) and D-malic acid doped KBO (DMA-KBO) were grown by the slow evaporation method at room temperature. The crystal structure has been confirmed by the single-crystal X-ray diffraction method. The understudied material's functional groups have been confirmed by Fourier Transform Infrared spectroscopy (FT-IR). Their optical parameters have been evaluated using UV-visible (UV-Vis) spectroscopy. UV-Vis spectroscopy revealed higher transmittance in the visible region, with band gap energies reported at 5.35 eV for pure KBO crystals and 5.65 eV for those doped with malic acid. Scanning electron microscopy (SEM) analysis explores the structural morphology of the grown crystal. Energy dispersive X-ray spectrometry (EDS) has been employed to validate the effective incorporation of malic acid. Thermogravimetric and differential thermal analysis (TGA/DTA) revealed that the doped crystals exhibited thermal superiority over the pure KBO. Laser damage analysis showed that doping enhanced the crystals' resistance to laser radiation.